Study on Reliability and Lifetime Prediction of High Power LEDs - Kailin Pan; Yu Guo; Weitao Zhu; Xin Wang; Bin Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the rapid development of semiconductor lighting technology, the LED will gradually replace the traditional lighting to be the lighting market-led. However, the reliability life of LED products is the key to restrict its development. For further study on the reliability in this paper, the stress accelerated test was adapt to explore the reliability of LED, meanwhile, the failure of failure devices in the test was analyzed, and to study the correlation between the contact thermal resistance change of the LED device structure and the light fades. The finite element software was applied to simulate the work load impact on LED, and the corresponding changes in the internal structure was analyzed as well , then the establishment of the internal structure of the strain and thermal resistance were built . Ultimately, a method which is significant to short the cycle of the LED life prediction was proposed based on the ANSYS simulation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4415